Changes in gut microbiota of gallstone mice at different altitudes based on 16S rDNA sequencing - Li, Song; Zhu, Wenjun; Guo, Runjie; Sun, Jinjin; Gao, Wei; Wu, Shile (Frontiers in Microbiomes, 2025)
ObjectiveTo establish a gallstone mouse model using a lithogenic diet and investigate changes in the gut microbiota of gallstone mice at different altitudes.MethodsSixty mice were randomly assigned to four groups: plain healthy, plain stone, high-altitude healthy, and high-altitude stone. Mice were raised in either plain or high-altitude environments, and a lithogenic diet was used to induce gallstone formation. After 8 weeks, the mice were euthanized, and stone formation was assessed. Blood samples were collected to measure serum total cholesterol (T-CHO), triglycerides (TG), and bile acid (TBA) levels. Fecal samples were also collected for 16S rDNA high-throughput sequencing to analyze the gut microbiota.ResultsTG and T-CHO levels were significantly elevated in gallstone mice in the plain and high-altitude groups. Differential microbiota analysis indicated a decrease in Bacteroidetes and an increase in Firmicutes in the gallstone groups. Several specific bacterial genera showed significant changes in the gallstone mice compared to the healthy controls.Conclusion1) Gut microbiota imbalance likely contributes to gallstone formation in mice, and higher microbiota diversity may reduce the incidence of gallstones. 2) The incidence of gallstones is higher at high altitudes than at lower altitudes, possibly due to hypoxic conditions and elevated inflammation levels.